Final answer:
To implement Euler's method, we need to rewrite equations (3) and (4a-c) in the form Vₘ₍ᵢ₊₁₎= Vₘ₍ᵢ₎ + h × f(Vₘ₍ᵢ₎, tₘ₍ᵢ₎). Equations (3) and (4a-c) can be rewritten as: Vₘ₍ᵢ₊₁₎ = Vₘ₍ᵢ₎ + h × f₁(Vₘ₍ᵢ₎, tₘ₍ᵢ₎), m₍ᵢ₊₁₎ = m₍ᵢ₎ + h × f₂(m₍ᵢ₎, tₘ₍ᵢ₎), n₍ᵢ₊₁₎ = n₍ᵢ₎ + h × f₃(n₍ᵢ₎, tₘ₍ᵢ₎), and h₍ᵢ₊₁₎ = h₍ᵢ₎ + h × f₄(h₍ᵢ₎, tₘ₍ᵢ₎).
Step-by-step explanation:
To implement Euler's method, we need to rewrite the equations in the form: Vₘ₍ᵢ₊₁₎= Vₘ₍ᵢ₎ + h × f(Vₘ₍ᵢ₎, tₘ₍ᵢ₎). Let's rewrite equations (3) and (4a-c) accordingly:
(3): Vₘ₍ᵢ₊₁₎ = Vₘ₍ᵢ₎ + h × f₁(Vₘ₍ᵢ₎, tₘ₍ᵢ₎)
(4a-c): m₍ᵢ₊₁₎ = m₍ᵢ₎ + h × f₂(m₍ᵢ₎, tₘ₍ᵢ₎)
n₍ᵢ₊₁₎ = n₍ᵢ₎ + h × f₃(n₍ᵢ₎, tₘ₍ᵢ₎)
h₍ᵢ₊₁₎ = h₍ᵢ₎ + h × f₄(h₍ᵢ₎, tₘ₍ᵢ₎)